Panorama de aproveitamento energético do biogás dos tratamentos de esgoto sanitário e de resíduos sólidos urbanos - Rodrigues, Larissa Jonaly (Universidade Federal de São Carlos, 2022)
Biogas is a sustainable alternative with great potential to be applied in the national energy scenario. This energy can be used as electrical, thermal, mechanical energy and converted into biomethane. In addition to the environmental contribution, the energy use of biogas guarantees the reuse of previously discarded resources. The sanitation sector is responsible for the largest volume of biogas produced, thus, this present research has the general objective of drawing an overview of the use of biogas from sanitation. For this, a review of the most recent literature was carried out, based on scientific documents published in the last decade. Through this analysis, it was observed that the application and production of biogas in Brazil is still compatible with it’s potential. It is believed that starting from the municipalities, the potential that biogas has today in Brazil can in fact go beyond mere expectations and become reality. It is therefore necessary that the public authorities create greater incentives for the production and implementation of biogas to reach the maximum of this potential, mainly through urban solid waste and sanitary sewage, thus contributing to the modernization and greater sustainability of the Brazilian energy matrix, also boosting the generation of employment and income, as well as greater economic potential for companies that implement the use of this product in their processes.
Overview of energy use of biogas from sewage treatment and urban solid waste treatment
Keywords: Biogás; Resíduos sólidos; Esgoto sanitário; Sustentabilidade; Matriz energética brasileira; Biogas; Solid waste; Sanitary sewage; Sustentability; Brazilian energy matrix; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA